Preferences for infrastructure and determinants of decision to live in a makeshift house in informal settlements - Eugene Ejike Ezebilo; Patrice Savadogo (Economies, 2021)
The upgrade paradigm has been a widely accepted solution to informal settlements. However, implementing an effective upgrade program has been challenging for governments of most developing countries. This paper reports a study which examined informal settlement residents' preferences for infrastructure provided by an upgrade project and factors influencing their decision to live in a makeshift house. It also examined how an informal settlement upgrade project can be implemented in an effective manner. The data originated from interviews with 231 residents of informal settlements in Port Moresby and was analyzed using mixed methods approach which includes descriptive statistics, qualitative content analysis and binary logistic regression model. The results show that all the residents would support the upgrade project and would pay for service charges associated with infrastructure and services provided by the project. Piped borne water and health care facility were the most preferred. In order for the upgrade project to be successful, residents should be fully involved in planning and implementing the project. Results from the logistic model revealed that decision to live in a makeshift house is influenced by factors such as house and land ownership, frequency of crime in the area, household size, occupation, access to toilet and number of years lived in informal settlement. There is a need to develop an effective mechanism for restricting the emergence of new informal settlements. The findings contribute to urban development planning by providing guidelines for upgrading informal settlements in an effective and efficient manner. The findings will be useful for policy makers, planners and urban development managers in the informal settlement upgrade process.
Keywords: 330; informal settlement; infrastructure; land use planning; settlement upgrade; urban development planning